Preparation, composition analysis and antioxidant activities of konjac oligo-glucomannan. (5th October 2015) - Liu, Jianhua; Xu, Qiuhong; Zhang, Jingjing; Zhou, Xuxia; Lyu, Fei; Zhao, Peicheng; Ding, Yuting
Highlights: Konjac oligo-glucomannan was prepared by degradation of konjac glucomannan. The average degree of polymerization of the konjac oligo-glucomannan was 5.2. FTIR spectra indicated that konjac glucomannan was successfully degraded. KOG exhibited significant antioxidant activities but weaker than Vc. Abstract: Konjac oligo-glucomannan (KOG) was prepared by degradation of konjac glucomannan (KG) using β-mannanase. The hydrolysis process was monitored by the viscosity of the enzymatic hydrolysates. Factors affecting the enzymatic hydrolysis of KG were investigated, and the optimum hydrolysis conditions were as follows: time 2 h; temperature 50 °C; pH 6.0; and enzymatic concentration 150 U/g. Under these optimized conditions, minimum viscosity (31.9 mPa·s) of the hydrolasate was obtained. The average degree of polymerization (DP) of the resulting KOG was approximately equal to 5.2. The results of Fourier transform infrared (FTIR) spectra of KG and KOG indicated that KG was successfully degraded. In addition, their antioxidant activities were evaluated by determination of hydroxyl radical (OH) and 1, 1-diphenyl-2-picrylhrazyl radical (DPPH) scavenging activity, and determination of reducing power. The results showed that KOG exhibited significant antioxidant activities. Taken together, this study suggested that KOG could potentially be used as a natural antioxidant.